Pre operative anxiety and its contributing factors in pediatric patients' parents undergoing surgery - Mehrdad Hosseinpour; Somayeh Abedi; Mohadese Hamsayeh; Bahareh Ahmadi (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Introduction: Hospitalization and surgery are among the most difficult experiences which children and their parents have to face. Many parents experience preoperative anxiety during the hospitalization of their children. This study attempts to assess preoperative anxiety in parents of children admitted for elective surgery and to evaluate factors associated with increased anxiety.  Material and Methods: In a cross-sectional study, all parents consecutively admitted to the study hospitals (Shahid Beheshti hospital in kashan and Imam Hossein hospital in Esfahan) were assessed. We used standard anxiety assessment questionnaires [Amsterdam Preoperative Anxiety and Information Scale (APAIS) and Spielberger's State-Trait Anxiety Inventory (STAI)] to quantify the anxiety of parents just before their child entered the operative theater. For mean comparison between variables, independent t-test, ANOVA and Chi-square analysis were used. Multiple regressions were conducted to determine the factors attributed to pre operative anxiety. A P-value of less than 0.05 was considered significant. Results: In this study 100 parents (60 cases from Shahid Beheshti hospital and 40 patients from Imam Hossein hospital) were evaluated. The mean anxiety score was 51.05±1.19 for STAI, 15.27±2.83 for APAIS (anxiety), and 8.07±1.7 for APAIS (information) respectively. Parents education was a factor that significantly affected the STAI (p=0.042), but its effect on APAIS was not significant. In regression analysis for anxiety severity, child age was a significant factor of anxiety status (p=0.043). Conclusions: This study showed that anxiety is relatively high in our centers and parent's education and children age are the most important predictive factors for this condition